Resolving the mesospheric nighttime 4.3 µm emission puzzle: Laboratory demonstration of new mechanism for OH(υ) relaxation - Konstantinos S. Kalogerakis; Daniel Matsiev; Ramesh D. Sharma; Peter P. Wintersteiner (Geophysical Research Letters)
Abstract We report laboratory results that support a recently proposed mechanism for relaxation of highly vibrationally excited hydroxyl radical by ground‐state oxygen atoms (Sharma et al., GRL 42, 4639–4647 (2015)). According to this mechanism, which eventually leads to an enhancement of nocturnal 4.3 µm CO2 emissions in the mesosphere, the deactivation of OH(high υ) by O(3P) involves a fast, spin‐allowed, multiquantum vibration‐to‐electronic (V‐E) energy transfer process generating O(1D). We present laser‐based experiments that demonstrate these energy transfer processes in action and discuss some implications of the new mechanism for mesospheric OH. These developments represent a breakthrough addressing the long‐standing problem of unacceptably large discrepancies between models and observations of the nocturnal mesospheric 4.3 µm emission.